Developing English Speech for Primary School Students (Eurasian Journal of Learning and Academic Teaching, 2022)
In this thesis, to increase the interest of primary school students in English and to give them an understanding in simple ways and to make effective use of exhibitions. It is about preventing the traditional flaws that students encounter in speech